Navigating People-Pleasing in “Dissect”: A Creative Autoethnographic Lens - Raja Dewangga Al'Dzaki (Universitas Sebelas Maret, 2024)
We believe that while many see niceness as mutually beneficial, few acknowledge the aspect of self-suffering. Previous theories identified this phenomenon as 'people-pleasing behavior,' wherein individuals were compelled to sacrifice their own feelings to fulfill the needs of others. Motivated to delve deeper, this creative project aimed to integrate the collective understanding of this issue into a novella titled “Dissect.” As the story unfolded, the central theme of the desire to break free from burdensome conformity to parental expectations was explored. This creative project aimed to provide a deeper understanding of the inherent difficulties associated with the tendency to please others through an examination of living with such inclination and how it led to acts of self-sacrifice as prompted within the narrative. Thus, this project used an autoethnographic approach to examine people-pleasing behavior. Similar to previous research that integrated personal experiences, this novella reflected the perspective of Lottie, the main character struggling with people-pleasing behavior, paralleling my own experiences. Through Lottie's journey of addressing people-pleasing behavior, this creative project revealed the detrimental effects of extreme people-pleasing, emphasizing that self-sacrifice was often a significant component demonstrating the extent of emotional and psychological investment individuals put into pleasing others.